Using finite element analysis to discuss the study of drawing of servo stamping curve - Dyi-Cheng Chen (SAGE Publishing, 2021)
This study employed different molding parameter combinations, the Taguchi method, ANOVA, and response surface methodology to perform experiments. Finite element analysis was executed to find the optimum molding parameters and increase the depth of drawing molding. The material is aluminum alloy 6016, and the servo press was adopted for the experiments. The factors influencing the drawing molding including punch fillet radius, die fillet radius, die clearance, molding curve, and mold temperature were determined. To find the optimum combination of parameters and to design 16 experimental combinations, the L16 orthogonal array of the Taguchi method was employed. According to the experimental results, the optimum parameters include punch fillet radius of 8.5 mm, die fillet radius of 8.5 mm, clearance of 1.5 t, curve 3, and the mold temperature of 20°C. Using the optimum parameter combination the molding depth could be increased greatly and the thickness ratio could be improved.